2014
DOI: 10.1371/journal.pone.0101159
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Screening of Children with Acute Malnutrition Requires a Change in Current WHO Guidelines as MUAC and WHZ Identify Different Patient Groups

Abstract: BackgroundTimely treatment of acute malnutrition in children <5 years of age could prevent >500,000 deaths annually. Screening at community level is essential to identify children with malnutrition. Current WHO guidelines for community screening for malnutrition recommend a Mid Upper Arm Circumference (MUAC) of <115 mm to identify severe acute malnutrition (SAM). However, it is currently unclear how MUAC relates to the other indicator used to define acute malnutrition: weight-for-height Z-score (WHZ).MethodsSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(139 citation statements)
references
References 13 publications
18
106
0
Order By: Relevance
“…The variation between WHZ and MUAC has also been reported by Laillou A et al 11 The report showed that using the WHO MUAC cut-off of 11.5 cm for screening, over 90% of children with a weight-for-height z-score (WHZ)<-3 were missed and WHZ < -3 missed 80% of the children with a MUAC of 11.5 cm. In our study, no subject with WHZ < -3 was identified by MUAC cut-off point contrary to the WHO report of similar prevalence of SAM when both MUAC and WHZ are compared.…”
Section: Cross Tabulation Of Frequencies Of Sam By Parameterssupporting
confidence: 55%
See 3 more Smart Citations
“…The variation between WHZ and MUAC has also been reported by Laillou A et al 11 The report showed that using the WHO MUAC cut-off of 11.5 cm for screening, over 90% of children with a weight-for-height z-score (WHZ)<-3 were missed and WHZ < -3 missed 80% of the children with a MUAC of 11.5 cm. In our study, no subject with WHZ < -3 was identified by MUAC cut-off point contrary to the WHO report of similar prevalence of SAM when both MUAC and WHZ are compared.…”
Section: Cross Tabulation Of Frequencies Of Sam By Parameterssupporting
confidence: 55%
“…18 There is a need to develop stand-alone parameters that can identify all malnourished children whether during screening in the field or in the clinics. Some authors 11,13 have suggested a MUAC of 13.5 cm and 15.5 cm as having a good sensitivity and specificity. Among the entire subject identified as SAM either by WHZ, BAZ or MUACZ, MUAC ranged from 11-15 cm.…”
Section: Cross Tabulation Of Frequencies Of Sam By Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In wasted children MUAC has often been used as a pre-screening tool, while W/H has been used to confirm the diagnosis. 6,7 Both anthropometric indices show an indirect reflection of fat and lean muscle catabolism that is obvious in SAM and are therefore the anthropometric measurements of choice in assessing the magnitude of malnutrition. 8 However, W/H requires the measuring of weight and height, as well as a reference table, while using MUAC requires only the use of a tape measure with a fixed cut off.…”
Section: Introductionmentioning
confidence: 99%